KARAKTERISTIKBATUAN METAMORF PAPALOANG -BACAN, HALMAHERA SELATAN, PROVINSI MALUKU UTARA - Madi, Almun; Alkatiri, Hilda; Firman, Firman (Journal of Science and Engineering, 2024)
The research location is in Papaloang village, Bacan Island, South Halmahera Regency, North Maluku Province. Metamorphic rocks in the Papaloang-Bacan Complex can be predicted as thermal dynamo metamorphic rocks (regional metamorphic), and are part of the Sibela Continental Suite which is Precambrian in age. The purpose of this study was to determine the characteristics of these rocks using petrographic methods, namely identifying texture, structure, and mineral content. Based on field observations and laboratory test results, metamorphic rocks in Papaloang are dominated by schist, mica schist, chlorite schist, chlorite-epidote schist, some phyllite, quartzite and gneiss with varying mineral compositions including biotite, hornblende/amphibolite, muscovite, tremolite-actinolite. Also filled with sulfide minerals such as pyrite, chalcopyrite, covellite and chalcocite as well as several iron oxide minerals. Foliation is relatively good, characterized by changes and interlocking of several minerals such as hornblende interlocking tremolite-actinolite, quartz interlocking iron oxide and Opak minerals, and changes in muscophite mica to biotite. This process is most likely related to high pressure from endogenous processes.